Unraveling the source of corrosive microorganisms from fracturing water to flowback water in shale gas field: evidence from gene sequencing and corrosion tests - Wang, Yanran; Wen, Shaomu; Zhang, Shibo; Tang, Yongfan; Yuan, Xi; Guan, Fang; Duan, Jizhou (Frontiers in Microbiology, 2025)
As an insidious and often underestimated phenomenon, microbially influenced corrosion (MIC) poses a significant threat to the integrity and longevity of oil and gas pipelines. However, the complex corrosive microorganisms, that might induce MIC in underground pipelines, might be introduced by the fracturing water during the production period, or they may also exist in the native corrosive microbial community underground. In this study, microbial community analysis was conducted to unravel the source of corrosive microbes in oil and gas pipelines. Meanwhile, the corrosion rate caused by the fracturing water and the flowback water on steel were studied via combining electrochemical analysis and weight loss analysis. Three types of fracturing fluids and the flowback water were analyzed based on 16S rRNA gene sequencing. Bacteria with multiple metabolic functions, including sulfate-reducing bacteria, acid producing bacteria, petroleum oil-degrading bacteria, and nitrate-reducing bacteria, were found in the flowback water. Comparative analysis on the fracturing fluids and the flowback water showed that corrosive Thermodesulfobacterium and DesulfobacterSota originated from the underground rocks. While other microorganisms such as Desulfomicrobium, Acinetobacter and Acetobacterium may be introduced via the fracturing water. The weight loss of steel coupons in fracturing and flowback water were 35.04±7.57 mpy and 28.07±4.49 mpy, respectively. The corrosion weight caused by the fracturing water may accounts for 75.16% of the whole corrosion during the 5 days’ immersion under laboratory conditions. The results provide a reference for tracing the sources of corrosive microorganisms and controlling microbially induced corrosion in shale gas resources.